ANALYSIS OF FACTORS AFFECTING THE INTEREST OF VISITING TOURISTS IN RELIGIOUS TOURISM DESTINATIONS SUNAN GUNUNG JATI - syaeful bakhri; Ega Triyana; Faridah Nurbaiti; Gunawan, Muhammad Fajar; Firdaus, Ahmad Maulana; Amelia Azizah; Mu’arif, Azmi Nizham; Muhammad Nuralam (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2023)
Religious tourism is one of the tours in Indonesia. Religious tourism is well known by most Indonesians considering the level of religion and culture inherent in Indonesian society. Cirebon is an area thick with tradition and culture, so it is known as the City of Religion. The icon of religious tourism in Cirebon is the Tomb of Sunan Gunung Jati which is a mandatory destination for religious tourists. The purpose of this research is to find out how religiosity, facilities, and tourist attraction can affect the interest of visitors. This study uses regression analysis as a quantitative approach. The population of this study is all tourists who visit Sunan Gunung Jati tourism. The sample of this study amounted to 96 respondents. Based on the analysis using the simultaneous significance test (F-test), the F-count value is 33,113 with a probability of 0.000, meaning that all independent variables, namely X1, X2, and X3 together have a significant effect on the dependent variable. The results showed that the dependent variable, namely the interest of visiting tourists in Sunan Gunung Jati tourism, was influenced by the independent variables, namely religiosity, facilities, and tourist attraction. Tourism managers are expected to maintain and maintain the condition of tourist facilities and increase visitor comfort. For further researchers, it is necessary to examine other variables that are not in this study, to analyze other factors that influence tourist interest.